Electron microscope sample preparation method for textile fiber cross-section observation
Patent Information
- Application Number
- CN202611033025.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-13
- Publication Date
- 2026-10-09
AI Technical Summary
[0002]目前,纺织纤维横截面切片制备主要依据标准FZ/T 01057.3-2007,规定了哈氏切片器与回转式切片机两种制样方式,然而哈氏切片器缺乏宏观标尺,切片厚度完全依赖技术员肉眼预估,切片过厚导致纤维横截面模糊不清,切片过薄则纤维易散落,均影响观察效果,回转式切片机的前处理涉及多种试剂依次处理,配比用时约需30min,操作效率低,且标准要求使用火棉胶作为纤维凝固定型试剂,该试剂存在易燃易爆、对眼睛、呼吸道粘膜具有刺激性、凝固时间较长等隐患
1、本方法所提供的一种纺织纤维横截面观察的电镜样品制备方法,无需添加任何有机溶剂、分散剂或固化剂,所需液氮亦能自然挥发,避免后续加热去除杂质的步骤,减少能耗,制备流程短,操作绿色简便。
Smart Images

Figure CN122882499A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of textile fiber surface morphology measurement technology, and in particular to a method for preparing electron microscope samples for cross-sectional observation of textile fibers. Background Technology
[0002] Currently, the preparation of cross-sectional sections of textile fibers mainly follows the standard FZ / T 01057.3-2007, which specifies two sample preparation methods: the Hastelloy microtome and the rotary microtome. However, the Hastelloy microtome lacks a macroscopic scale, and the section thickness relies entirely on the technician's visual estimation. If the section is too thick, the fiber cross-section will be unclear, and if the section is too thin, the fiber will easily scatter, both affecting the observation effect. The pretreatment of the rotary microtome involves the sequential processing of multiple reagents, and the preparation time is about 30 minutes, resulting in low operating efficiency. Moreover, the standard requires the use of collodion as a fiber coagulation and fixation reagent, which poses risks such as being flammable and explosive, irritating to the eyes and respiratory mucosa, and having a long coagulation time.
[0003] Currently, some studies have attempted to use resin embedding as an alternative to collodion. This method can reduce fiber cross-sectional deformation and improve image clarity and fiber dispersion. However, resin embedding still has certain limitations, such as the need to stir the embedding agent for more than 5 hours, and the overall sample preparation time is much longer than that of traditional methods.
[0004] Therefore, how to shorten sample preparation time and improve the clarity of cross-sectional structure has become an urgent problem to be solved. Summary of the Invention
[0005] This invention provides a method for preparing electron microscopy samples for cross-sectional observation of textile fibers, which can shorten sample preparation time and improve the clarity of cross-sectional structures.
[0006] A first aspect of the present invention provides a method for preparing an electron microscope sample for cross-sectional observation of textile fibers, comprising: Textile fibers are obtained using a sampling tool and placed on a first metal substrate. The first metal substrate is then fixed inside the preparation container at a preset depth. Liquid nitrogen is injected into the preparation container, and when the liquid nitrogen has completely evaporated, the textile fibers are cut to obtain cut fibers. The cutting fiber is transferred to the second metal substrate using the sampling tool, and the cutting fiber is fixed with conductive adhesive to obtain the test sample.
[0007] Optionally, in one possible implementation of the first aspect, the step of placing the textile fibers obtained based on the sampling tool onto the first metal substrate includes: A first adhesive conductive adhesive is obtained by selecting a conductive adhesive, and a metal substrate is coated based on the first adhesive conductive adhesive to obtain a first metal substrate; A predetermined mass of textile fibers is transferred using a sampling tool and placed onto a first metal substrate.
[0008] Optionally, in one possible implementation of the first aspect, selecting the conductive adhesive to obtain the first adhesive conductive adhesive includes: Conductive adhesives include gold conductive adhesives, silver conductive adhesives, copper conductive adhesives, and carbon conductive adhesives; The first adhesive conductive adhesive is obtained by selecting the conductive adhesive according to the preset conductive adhesive type.
[0009] Optionally, in one possible implementation of the first aspect, coating the metal substrate based on the first adhesive conductive adhesive to obtain the first metal substrate includes: Metal substrates include aluminum, copper, and aluminum-magnesium alloys; A reference metal substrate is obtained by selecting a metal substrate based on a preset metal type; The first conductive adhesive is coated onto the reference metal substrate to obtain the first metal substrate.
[0010] Optionally, in one possible implementation of the first aspect, the step of placing a predetermined mass of textile fibers onto a first metal substrate using a sampling tool includes: Textile fibers include fibers with circular cross-sections, oval cross-sections, and irregular cross-sections; A reference textile fiber is obtained by selecting textile fibers based on a preset cross-section type, and a preset mass of the reference textile fiber is transferred to a first metal substrate using a sampling tool.
[0011] Optionally, in one possible implementation of the first aspect, fixing the first metal substrate within the preparation container based on a preset depth includes: Fixed containers include metal containers, stainless steel containers, glass containers, and paper cups.
[0012] A preparation container is obtained by selecting a fixed container, a preset depth is determined according to the preparation container, and the first metal substrate is fixed in the preparation container based on the preset depth.
[0013] Optionally, in one possible implementation of the first aspect, determining the preset depth based on the preparation container includes: Obtain the height of the prepared container and use the container height as the preset depth.
[0014] Optionally, in one possible implementation of the first aspect, the step of injecting liquid nitrogen into the preparation container and, after determining that the liquid nitrogen has completely evaporated, cutting the textile fibers to obtain cut fibers includes: Liquid nitrogen was injected into the preparation container until the reference textile fibers were submerged in the liquid nitrogen, and then the container was left to stand. After confirming that the liquid nitrogen has evaporated and disappeared, the longitudinal direction of the vertical reference textile fiber is taken as the cutting direction; The reference textile fiber is cut using a cutting tool along the cutting direction to obtain the cut fiber.
[0015] Optionally, in one possible implementation of the first aspect, the step of transferring the cut fiber onto a second metal substrate using the sampling tool and fixing the cut fiber with conductive adhesive to obtain the test sample includes: The metal substrate is selected to obtain a second metal substrate, and a conductive adhesive is selected to obtain a second fixed conductive adhesive; The cut fiber is transferred to the second metal substrate, and the cut fiber is fixed with conductive adhesive based on the alignment result of the substrate edges of the cut fiber and the second metal substrate to obtain the test sample.
[0016] Optionally, in one possible implementation of the first aspect, the substrate edge alignment result based on the cut fiber and the second metal substrate is used to fix the cut fiber with conductive adhesive to obtain the test sample, including: The comparison results are obtained by comparing the cross-sectional head end of the cut fiber with the edge of the substrate; When the comparison result is determined to be an alignment result, and the length direction of the cut fiber is parallel to the substrate surface of the second metal substrate, the cut fiber is fixed with conductive adhesive to obtain the test sample.
[0017] The beneficial effects of this invention are as follows: 1. The method provided here is an electron microscopy sample preparation method for observing the cross-section of textile fibers. It does not require the addition of any organic solvents, dispersants or curing agents. The required liquid nitrogen can also evaporate naturally, avoiding the subsequent heating to remove impurities, reducing energy consumption, and the preparation process is short, green and simple to operate.
[0018] 2. The preparation method of the present invention has a simple and quick sample preparation process, which only takes 35 to 40 seconds, shortening the sample preparation time and improving the preparation efficiency.
[0019] 3. The test sample obtained by the preparation method of the present invention has well dispersed fibers, clear cross-sectional structure, distinct boundaries, and obvious characteristics, which facilitates accurate identification of fiber types. Attached Figure Description
[0020] Figure 1 A flowchart of a method for preparing an electron microscope sample for cross-sectional observation of textile fibers provided by the present invention; Figure 2 The scanning electron microscope image of Experiment 1 provided by this invention; Figure 3 The scanning electron microscope image of Experiment 2 provided by this invention; Figure 4 The scanning electron microscope image of Experiment 3 provided by this invention; Figure 5 The scanning electron microscope image of Experiment 4 provided by this invention; Figure 6 The image is a scanning electron microscope image of the comparative experiment provided by this invention. Detailed Implementation
[0021] To make the objectives, technical solutions, and advantages of the embodiments of the present invention clearer, the technical solutions of the embodiments of the present invention will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.
[0022] The terms "first," "second," "third," "fourth," etc. (if present) in the specification, claims, and accompanying drawings of this invention are used to distinguish similar objects and are not necessarily used to describe a specific order or sequence. It should be understood that such data can be interchanged where appropriate so that embodiments of the invention described herein can be implemented in orders other than those illustrated or described herein.
[0023] It should be understood that in the various embodiments of the present invention, the sequence number of each process does not imply the order of execution. The execution order of each process should be determined by its function and internal logic, and should not constitute any limitation on the implementation process of the embodiments of the present invention.
[0024] It should be understood that in this invention, "comprising" and "having" and any variations thereof are intended to cover non-exclusive inclusion, for example, a process, method, system, product or device that includes a series of steps or units is not necessarily limited to those steps or units that are explicitly listed, but may include other steps or units that are not explicitly listed or that are inherent to such process, method, product or device.
[0025] The technical solution of the present invention will be described in detail below with reference to specific embodiments. These specific embodiments can be combined with each other, and the same or similar concepts or processes may not be described again in some embodiments.
[0026] like Figure 1 As shown, the present invention provides a method for preparing electron microscopy samples for cross-sectional observation of textile fibers, comprising: S1, textile fibers are obtained using a sampling tool and placed on a first metal substrate, and the first metal substrate is fixed in the preparation container at a preset depth.
[0027] Understandably, a certain amount of textile fibers is placed on a clean metal substrate coated with conductive adhesive using tweezers, and the metal substrate is fixed inside the preparation container, with the fixing depth being the same as the height of the container.
[0028] The sampling tool is a tool for extracting textile fibers, such as tweezers. The first metal substrate is a metal substrate placed before fiber cutting. The preset depth is the depth of the fixed substrate determined according to the preparation container. The preparation container is a container for fixing the metal substrate.
[0029] In some embodiments, the specific implementation of step S1 includes: S11, Select the conductive adhesive to obtain the first adhesive conductive adhesive, and coat the metal substrate based on the first adhesive conductive adhesive to obtain the first metal substrate.
[0030] Understandably, since there are many types of conductive adhesives, when preparing a test sample with a fully exposed cross-section, it is necessary to select one of the various conductive adhesives as the first adhesive to adhere to the first metal substrate.
[0031] In some embodiments, the specific implementation of step S11 includes: S111, conductive adhesives include gold conductive adhesive, silver conductive adhesive, copper conductive adhesive, and carbon conductive adhesive.
[0032] It is understandable that different metals have different electrical conductivity, therefore, there are various conductive adhesives corresponding to different metals.
[0033] S112, Select the first adhesive conductive adhesive according to the preset conductive adhesive type to obtain the first adhesive conductive adhesive.
[0034] It is understandable that the preset conductive adhesive type is a type of conductive adhesive that is predetermined by human intervention, such as gold conductive adhesive, and the first adhesive is the conductive adhesive corresponding to the preset conductive adhesive type, such as gold conductive adhesive.
[0035] S113, the metal substrate includes aluminum, copper, and aluminum-magnesium alloy.
[0036] It is understandable that metal substrates include various types of substrates, such as aluminum, copper, and aluminum-magnesium alloys, and one of these metal substrates can be selected as the first metal substrate.
[0037] S114, Select a reference metal substrate based on a preset metal type.
[0038] It is understandable that the preset metal type is a pre-determined metal substrate type, and the reference metal substrate is a substrate selected from a variety of metal substrates, such as a copper metal substrate.
[0039] S115, the first adhesive conductive adhesive is coated onto the reference metal substrate to obtain the first metal substrate.
[0040] It is understandable that the selected first adhesive conductive adhesive is coated onto the reference metal substrate to obtain a first metal substrate with the first adhesive conductive adhesive.
[0041] S12, a preset mass of textile fibers is transferred using a sampling tool and placed on a first metal substrate.
[0042] It is understandable that the preset quality is the quality of the fiber being transferred, which is set in advance.
[0043] In some embodiments, the specific implementation of step S12 includes: S121, textile fibers include fibers with circular cross-section, oval cross-section, and irregular cross-section.
[0044] S122, a reference textile fiber is obtained by selecting textile fibers based on a preset cross-section type, and a preset mass of the reference textile fiber is transferred to the first metal substrate according to a sampling tool.
[0045] Understandably, a reference textile fiber for preparing the test sample is obtained by selecting a fiber with a cross-section type from among various types of textile fibers, and then using tweezers to transfer a preset mass of the reference textile fiber onto the first metal substrate.
[0046] The preset cross-section type is a pre-determined cross-section type for the fiber, such as a circular cross-section.
[0047] S13, The fixed container is a metal container, a stainless steel container, a glass container, or a paper cup.
[0048] It is understood that a fixed container is a container that fixes a first metal base, including metal containers, stainless steel containers, glass containers, and paper cups.
[0049] S14, a preparation container is obtained by selecting a fixed container, a preset depth is determined according to the preparation container, and the first metal substrate is fixed in the preparation container based on the preset depth.
[0050] Understandably, one type of container is selected from a variety of fixed containers as the preparation container for fixing the metal substrate, so as to fix the first metal substrate inside the container.
[0051] The preparation container is a container that fixes the first metal substrate, namely, a metal container, a stainless steel container, a glass container, or a paper cup.
[0052] In some embodiments, the specific implementation of step S14 includes: S141, Obtain the container height of the preparation container, and use the container height as the preset depth.
[0053] It is understandable that the container height is the same as the height of the preparation container.
[0054] S2, liquid nitrogen is injected into the preparation container, and when the liquid nitrogen has completely evaporated, the textile fiber is cut to obtain cut fiber.
[0055] It is understandable that cut fiber refers to the fiber obtained by cutting textile fibers.
[0056] In some embodiments, the specific implementation of step S2 includes: S21, Liquid nitrogen is injected into the preparation container until the liquid nitrogen immerses the reference textile fiber and then it is left to stand.
[0057] Understandably, since the first metal substrate containing the reference textile fiber is placed in a fixed container, the reference textile fiber needs to be immersed in liquid nitrogen when liquid nitrogen is injected into the preparation container in order to allow the fiber to be cooled by liquid nitrogen.
[0058] S22, after determining that the liquid nitrogen has evaporated and disappeared, the longitudinal direction of the vertical reference textile fiber is taken as the cutting direction.
[0059] Understandably, after the liquid nitrogen has been left to stand for a period of time to evaporate, the reference textile fiber can be cut in a direction perpendicular to the longitudinal direction of the reference textile fiber.
[0060] S23, the reference textile fiber is cut along the cutting direction using a cutting tool to obtain cut fiber.
[0061] Understandably, the cutting tool is a clean, sharp blade.
[0062] S3, the cut fiber is transferred to the second metal substrate using the sampling tool, and the cut fiber is fixed with conductive adhesive to obtain the test sample.
[0063] Understandably, the second metal substrate is a metal substrate on which the cut fibers are placed, and the test sample is a fiber with its cross-section fully exposed.
[0064] In some embodiments, the specific implementation of step S3 includes: S31, Select the metal substrate to obtain a second metal substrate, and select conductive adhesive to obtain a second fixed conductive adhesive.
[0065] It is understandable that when the reference textile fiber is cut to obtain the cut fiber, the cut fiber can be transferred to the second metal substrate. The second metal substrate is determined in the same way as the first metal substrate. The selection of conductive adhesive to obtain the second fixing conductive adhesive is the same as the first adhesive conductive adhesive, both of which are selected manually.
[0066] The second type of conductive adhesive is a conductive adhesive used to fix the cut fibers.
[0067] S32, the cut fiber is transferred to the second metal substrate, and the cut fiber is fixed with conductive adhesive based on the alignment result of the substrate edges of the cut fiber and the second metal substrate to obtain the test sample.
[0068] It is understandable that when fixing the cut fiber, the front end of the cross section of the cut fiber needs to be aligned with the edge of the base of the second metal substrate. Therefore, only when the alignment result is obtained can the cut fiber be fixed with conductive adhesive to obtain the test sample.
[0069] The base edge is the edge of the second metal base.
[0070] In some embodiments, the specific implementation of step S32 includes: S321, compare the cross-sectional head end of the cut fiber with the edge of the substrate to obtain the comparison result.
[0071] It is understandable that the front end of the cross section is the end of the cut fiber corresponding to the exposed cross section, and the comparison result is the result of comparing whether the front end of the cross section and the edge of the substrate are aligned.
[0072] S322, when the comparison result is determined to be an alignment result and the length direction of the cut fiber is parallel to the substrate surface of the second metal substrate, the cut fiber is fixed with conductive adhesive to obtain the test sample.
[0073] Understandably, when the comparison result is an alignment result and the length direction of the cut fiber is parallel to the substrate surface of the second metal substrate, the cut fiber is fixed with conductive adhesive to obtain the test sample.
[0074] The above preparation method allows for the preparation of test samples with fully exposed cross-sections by using liquid nitrogen cooling and blade cutting, enabling clear observation of the fiber cross-section shape under an electron microscope, and also provides a short preparation time.
[0075] It is worth mentioning that this invention can select different fibers, metal substrates, and conductive adhesives to prepare test samples, and use scanning electron microscopy to detect the above-mentioned test samples. The different experiments are respectively named Experiment 1, Experiment 2, Experiment 3, Experiment 4, and a comparative experiment. The specific experimental procedures are as follows: Experiment 1: A small amount of polyester fiber is transferred using tweezers and placed on a clean copper metal substrate adhered with gold conductive adhesive. The copper metal substrate is then fixed inside a paper cup, with the copper metal substrate at the same height as the paper cup. Liquid nitrogen is injected into the paper cup until the polyester fiber is submerged. After standing for a certain period of time, the liquid nitrogen naturally... After the evaporation is complete, the polyester fiber is quickly cut with a clean, sharp blade in a direction perpendicular to the longitudinal direction of the polyester fiber. Using tweezers, the cut polyester fiber is transferred to a clean copper metal substrate coated with gold conductive adhesive, ensuring the end of the polyester fiber cross-section is flush with the edge of the copper metal substrate and the length of the polyester fiber is parallel to the surface of the copper metal substrate. The polyester fiber is then fixed with gold conductive adhesive, thus obtaining a test sample with a fully exposed cross-section. The entire sample preparation process in Experiment 1 took 35 seconds. The sample was then examined using a scanning electron microscope (SEM). The polyester test sample was gold-coated and placed in the SEM chamber of a Quanta 600 FEG cold field emission scanning electron microscope. The parameters were set as follows: accelerating voltage 20 kV, accelerating current 10 µA, working distance 8.8 mm, and magnification adjusted to 10,000x and 20,000x. The results are shown below. Figure 2 The scanning electron microscope image shown clearly reveals that the cross-section of the polyester fiber is circular, in which... Figure 2 In the image, a1 and a2 (both numbers 1 and 2 need to be subscripted) are the images after adjusting the magnification to 10000x and 20000x, respectively.
[0076] Experiment 2 was similar to Experiment 1, except that before fiber cutting, the textile fibers were Coolmax fibers, the conductive adhesive was silver conductive adhesive, and the metal substrate was aluminum. After fiber cutting, the textile fibers were Coolmax fibers, the conductive adhesive was silver conductive adhesive, and the metal substrate was aluminum. The sample preparation process in Experiment 2 took 40 seconds. The sample was then examined using a scanning electron microscope (SEM). The Coolmax sample was gold-coated and placed in the chamber of a Quanta 600 FEG cold field emission scanning electron microscope. The parameters were set as follows: accelerating voltage 20 kV, accelerating current 10 µA, working distance 10.2 mm, and magnification adjusted to 5000x and 10000x. The results were as follows. Figure 3 The scanning electron microscope image shown clearly reveals that the cross-section of Coolmax fibers is a flattened cross shape, in which... Figure 3 In the image, a1 and a2 (both numbers 1 and 2 need to be subscripted) are the images after adjusting the magnification to 5000x and 10000x, respectively.
[0077] Experiment 3 was similar to Experiment 1, except that the textile fibers used before cutting were Coolsmart fibers and the conductive adhesive was copper conductive adhesive, while the textile fibers used after cutting were also Coolsmart fibers and the conductive adhesive was copper conductive adhesive. The sample preparation process in Experiment 3 took a total of 40 seconds. The sample was then examined using a scanning electron microscope (SEM). Specifically, the Coolsmart sample was gold-coated and placed in the chamber of a Quanta 600 FEG cold field emission scanning electron microscope. The parameters were set as follows: accelerating voltage 20 kV, accelerating current 10 µA, working distance 10.0 mm, and magnification adjusted to 5000x and 10000x. The results were as follows. Figure 4 The scanning electron microscope image shown clearly reveals that the cross-section of Coolsmart fibers is a regular cross shape, in which... Figure 4 In the image, a1 and a2 (both numbers 1 and 2 need to be subscripted) are the images after adjusting the magnification to 5000x and 10000x, respectively.
[0078] Experiment 4 was similar to Experiment 1, except that the textile fiber used was cotton fiber. The sample preparation process in Experiment 4 took 35 seconds. The sample was then examined using a scanning electron microscope (SEM). Specifically, the cotton fiber sample was sputter-coated with gold and placed in the chamber of a Quanta 600 FEG cold field emission scanning electron microscope. The parameters were set as follows: accelerating voltage 10 kV, accelerating current 10 µA, working distance 10.0 mm, and magnification adjusted to 5000x and 10000x. The results were as follows. Figure 5 The scanning electron microscope image shown clearly reveals that the cross-section of the cotton fiber is oval, in which... Figure 5 In the image, a1 and a2 (both numbers 1 and 2 need to be subscripted) are the images after adjusting the magnification to 5000x and 10000x, respectively.
[0079] The comparative experiment used an existing preparation method, which involved mixing methyl methacrylate (MMA) and n-butyl methacrylate (BMA) at a volume ratio of 3:2.6, adding a small amount of polymethyl methacrylate (PMMA), and stirring on a thermostatic magnetic stirrer for about 5 hours to ensure that the PMMA was fully dissolved in the MMA / BMA mixed monomers. Then, 1% (by the total weight of the embedded monomers) of benzoyl peroxide (BPO) was added to the embedding monomer solution, and after stirring for half an hour, the desired embedding agent was obtained. The two ends of an appropriate amount of Coolsmart fiber were fixed with sewing thread, and the prepared sample was placed into a polypropylene tube sealed at one end. The embedding agent was then poured into the polypropylene tube. The sample was placed in a vacuum desiccator and evacuated. The other end of the polypropylene tube was then sealed. After sealing, the Coolsmart fibers were kept parallel and straight within the rigid plastic tube by pulling the sewing thread. The prepared sample was placed in an oven and polymerized at 65°C for 8 hours to obtain the Coolsmart fiber embedding. The polypropylene tube was removed, and the Coolsmart fiber embedding was taken out and sliced on the stage of a hand-cranked microtome to obtain the test sample. The total preparation time for the comparative experiment was 14 hours. The sample was then analyzed using a scanning electron microscope (SEM). The Coolsmart test sample was sputtered with gold and placed on a clean metal substrate coated with conductive adhesive. The SEM images were observed in the chamber of a Quanta 600 FEG cold field emission scanning electron microscope. The accelerating voltage in the chamber was 20 kV, the accelerating current was 10 µA, the working distance was 9.9 mm, and the magnification was adjusted to 1000x and 5000x. Figure 6 The scanning electron microscope images shown reveal that the cross-section of Coolsmart fibers prepared by the resin embedding method is deformed, and the cross-sectional boundaries are unclear, which is detrimental to the identification of the fiber cross-section. Figure 6 In the image, a1 and a2 (both numbers 1 and 2 need to be subscripted) are the images after adjusting the magnification to 1000x and 5000x, respectively.
[0080] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, and not to limit them; although the present invention has been described in detail with reference to the foregoing embodiments, those skilled in the art should understand that modifications can still be made to the technical solutions described in the foregoing embodiments, or equivalent substitutions can be made to some or all of the technical features; and these modifications or substitutions do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.
Claims
1. A method for preparing electron microscopy samples for cross-sectional observation of textile fibers, characterized in that, include: Textile fibers are obtained using a sampling tool and placed on a first metal substrate. The first metal substrate is then fixed inside the preparation container at a preset depth. Liquid nitrogen is injected into the preparation container, and when the liquid nitrogen has completely evaporated, the textile fibers are cut to obtain cut fibers. The cutting fiber is transferred to the second metal substrate using the sampling tool, and the cutting fiber is fixed with conductive adhesive to obtain the test sample.
2. The method according to claim 1, characterized in that, The step of obtaining textile fibers based on a sampling tool and placing them on a first metal substrate includes: A first adhesive conductive adhesive is obtained by selecting a conductive adhesive, and a metal substrate is coated based on the first adhesive conductive adhesive to obtain a first metal substrate; A predetermined mass of textile fibers is transferred using a sampling tool and placed onto a first metal substrate.
3. The method according to claim 2, characterized in that, The process of selecting the conductive adhesive to obtain the first adhesive conductive adhesive includes: Conductive adhesives include gold conductive adhesives, silver conductive adhesives, copper conductive adhesives, and carbon conductive adhesives; The first adhesive conductive adhesive is obtained by selecting the conductive adhesive according to the preset conductive adhesive type.
4. The method according to claim 3, characterized in that, The process of coating a metal substrate with the first conductive adhesive to obtain a first metal substrate includes: Metal substrates include aluminum, copper, and aluminum-magnesium alloys; A reference metal substrate is obtained by selecting a metal substrate based on a preset metal type; The first conductive adhesive is coated onto the reference metal substrate to obtain the first metal substrate.
5. The method according to claim 2, characterized in that, The step of transferring a preset mass of textile fibers using a sampling tool and placing them onto a first metal substrate includes: Textile fibers include fibers with circular cross-sections, oval cross-sections, and irregular cross-sections; A reference textile fiber is obtained by selecting textile fibers based on a preset cross-section type, and a preset mass of the reference textile fiber is transferred to a first metal substrate using a sampling tool.
6. The method according to claim 1, characterized in that, The step of fixing the first metal substrate within the preparation container at a preset depth includes: Fixed containers include metal containers, stainless steel containers, glass containers, and paper cups. A preparation container is obtained by selecting a fixed container, a preset depth is determined according to the preparation container, and the first metal substrate is fixed in the preparation container based on the preset depth.
7. The method according to claim 6, characterized in that, Determining the preset depth based on the preparation container includes: Obtain the height of the prepared container and use the container height as the preset depth.
8. The method according to claim 5, characterized in that, The step of injecting liquid nitrogen into the preparation container and, after confirming that the liquid nitrogen has completely evaporated, cutting the textile fibers to obtain cut fibers includes: Liquid nitrogen was injected into the preparation container until the reference textile fibers were submerged in the liquid nitrogen, and then the container was left to stand. After confirming that the liquid nitrogen has evaporated and disappeared, the longitudinal direction of the vertical reference textile fiber is taken as the cutting direction; The reference textile fiber is cut using a cutting tool along the cutting direction to obtain the cut fiber.
9. The method according to claim 1, characterized in that, The step of transferring the cut fiber onto a second metal substrate using the sampling tool and fixing the cut fiber with conductive adhesive to obtain the test sample includes: The metal substrate is selected to obtain a second metal substrate, and a conductive adhesive is selected to obtain a second fixed conductive adhesive; The cut fiber is transferred to the second metal substrate, and the cut fiber is fixed with conductive adhesive based on the alignment result of the substrate edges of the cut fiber and the second metal substrate to obtain the test sample.
10. The method according to claim 9, characterized in that, The substrate edge alignment result based on the cut fiber and the second metal substrate is used to fix the cut fiber with conductive adhesive to obtain the test sample, including: The comparison results are obtained by comparing the cross-sectional head end of the cut fiber with the edge of the substrate; When the comparison result is determined to be an alignment result, and the length direction of the cut fiber is parallel to the substrate surface of the second metal substrate, the cut fiber is fixed with conductive adhesive to obtain the test sample.